Squamous atipical cells do undetermined significance: a literature review - Pedrosa, Michele L.; Mattos, Inês E.; Koifman, Rosalina J.; Silva, Ricardo José O.; Athayde, Maria José P.M. (Brazilian Journal of Sexually Transmitted Diseases, 2003)
Atypical squamous cells of undetermined significance are the most prevalent abnormalities observed in smears performed in screening for cervical cân cer. The management of women with ASCUS is particularly problematic because it can mean reactive, preinvasive or invasive disease. This study pre- sent a up to date revision of literature about ASCUS, showing the differents follows up for women with this cytologic diagnosis.